Epigrams and Criticisms in Miniature - Sullivan, William Laurence (University of Pennsylvania Press, 2017)
Brief and original comment on Society and Institutions; Imagination, Heart, and Will; Reflection and Philosophy; and Religion, together with criticisms on various literary figures, philosophers, and public men.